ISLAM BEYOND TERRORISTS AND TERRORISM : Biographies of the Most Influential Muslims in History - Mahmood, Iftekhar (University Press of America, 2002)
Recent incidents in the United States have drawn much attention towards Islam and its followers. Unfortunately, these incidents combined with the public's lack of knowledge about Islam and its intellectual heritage have caused many to view Islam in a negative light. In Islam Beyond Terrorists and Terrorism, Dr. Iftekhar Mahmood provides readers with a brief introduction to the life and contributions of the most influential Muslims throughout history. Dr. Mahmood details the lives of various Muslim scholars, scientists, philosophers, writers, politicians, rulers, religious figures, and military commanders, in an effort to educate both Muslims and non-Muslims